HUBUNGAN PARITAS DENGAN TINGKAT PENGTAHUAN TENTANG PERAWATAN MASA NIFAS DI TPMB WILAYAH MUNTILAN - Sholaikhah Sulistyoningtyas; Belian Anugrah Estri (Jurnal Kesehatan, 2025)
One way to see success in efforts to improve maternal and child health is with high and low maternal mortality rates (AKI). In addition to assessing maternal health programs, this indicator is also able to assess the degree of public health, because of its sensitivity to improving health services, both in terms of accessibility and quality To reduce mortality and morbidity, it is necessary to pay attention to health during the postpartum period. Health during the postpartum period greatly affects the sustainability of health for mothers and babies. During the postpartum period, the mother experiences various changes both physiological and psychological as well as basic needs and care during the postpartum period to accelerate the recovery period. The purpose of this study is to find out if there is a relationship between parity and the level of care about postpartum care in PMB Muntilan Region. The research method with . This study is a quantitative research with a correlation analytical method and a Cross Sectional approach. with a sample of 33 respondents. Respondents in this study were postpartum mothers 1-7 days postpartum in PMB in the Muntilan area. Data analysis to determine the correlation results of this research data using spearman rank analysis. The results of this study obtained a p value, 0.05, so it can be concluded that there is a parity relationship with the level of knowledge about postpartum care. It is hoped that mothers both primi and multipara will further increase their knowledge related to postpartum care to prevent complications during the postpartum period. By paying close attention to the counseling provided by the Health Tenga when visiting during postpartum.